Inoculation and counterexplanation debiasing techniques in the perseverance of social theories - Anderson, Craig A.
Our social theories are often unresponsive to logical and empirical challenges. Earlier research has demonstrated that the process of creating causal explanations or general scenarios to explain observed events contributes to such unwarranted theory perseverance. An analyses of possible cognitive mechanisms underlying theory perseverance suggests that explanation processes might be used in "debiasing" techniques. It is predicted that theory perseverance would be reduced by including subjects to create causal explanations for both possible relationships between two social variables. Colleges students were given two case studies suggestive of either a positive or a negative relationships between preference for risk and success as a firefighter. Some subjects had only to consider the relationship suggested by their case history data. Others were induced to considered both possible relationships. Subjects forced to consider both relationships showed significantly less theory perseverance, supporting the analysis of the cognitive mechanisms underlying theory perseverance and suggesting possible applications in real-world contexts. The probable lucos of the effects of the debiasing techniques and possible boundary conditions are discussed.